Epicuticular Wax Content on Leaf Epidermis of Selected Brassica L. Taxa in Relation to Feeding Behaviour Against Diamondback Moth, Plutella xylostella L. (Lepidoptera: Plutellidae) Larvae - Talip, Noraini; Ahmad, Syamsurina; Abd Ghani, Idris; Ghazalli, Mohd Norfaizal; Zohari, Ahmad Fitri; Basir, Nur Syazwani (Semarak Proceedings of Natural and Environmental Sciences, 2026)
Many aspects of epicuticular waxes have been studied over the years. In plants, the epicuticular wax layer provides a protective barrier, which consists predominantly of long-chain hydrocarbon compounds, including alkanes, primary alcohols, aldehydes, secondary alcohols, ketones, esters, and other derived compounds. However, there is a limited understanding of the relationship between animal or insect-eating habits and plant micromorphological characteristics. This study investigated the impact of epicuticular wax content in five selected taxa of Brassica L. on the feeding behaviour of diamondback moth (DBM), Plutella xylostella L., using observation under the scanning electron microscope (SEM). The findings have revealed that the epicuticular waxes' morphology content was composed primarily of rodlets, flakes, thread-like, granular, and smooth film coating. The analysis was conducted using a one-way analysis of variance (ANOVA). Findings have shown that there was a significant difference regarding the time spent on feeding by the larvae of the 3rd instar of the DBM both in choice (F = 510.58, df = 5 & 54, P < 0.05) and no-choice tests (F = 38.92, df = 5 & 54, P < 0.05) to the epicuticular wax content in Brassica leaves. These insect pests showed a weak preference for leaves with high epicuticular wax. It was concluded that the variation in waxes present in the Brassica taxa studied has great significance as a mechanical barrier to the DBM larvae.